Pemberian Layanan Bimbingan dan Konseling Dalam Menangani Unfinished Business Pada Peserta Didik di SMP Islam Al-Ikhlas - Khoirunnisa Miftahul Jannah; Yusuf Maulana (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
This study aims to explore the provision of Guidance and Counseling Services at SMP Islam Al-Ikhlas (Al-Ikhlas Islamic Junior High School), with a focus on handling unfinished business among students. The term unfinished business refers to unresolved emotional problems, such as trauma from bullying and social pressure, which have a negative impact on students’ psychological well-being. This study uses individual counseling services with a fantasy approach from gestalt counseling to help students express pent-up problems and emotions. In addition, brainstorming and assertive skill development methods were applied in group guidance and counseling sessions to encourage students to share experiences, provide feedback, and express opinions with confidence. The results show that guidance and counseling plays an important role in developing students’ ability to deal with emotions, build confidence, and express their emotions better.